Self-reported sleep quality and depression in post myocardial infarction patients attending cardiology outpatient clinics in Oman - Rashid Said Saif Almamari; Joshua Kanaabi Muliira; Eilean Rathinasamy Lazarus (Elsevier, 2019)
Objective: This study aimed to examine the sleep quality and prevalence of depression in post myocardial infarction patients attending cardiology outpatient clinics of selected hospitals in Oman. Methods: A descriptive cross-sectional design was used to collect data from patients (n = 180) who were at least 4 weeks post myocardial infarction diagnosis and receiving follow-up care in the outpatient clinic. The Arabic version of the Pittsburgh Sleep Quality Index and Patient Health Questionnaire-9 were used to assess sleep quality and depressive symptoms, respectively. Results: The sample mean age was 62.0 ± 11.3 years. Poor sleep quality affected 61.1% of the participants. The significant predictors of poor sleep quality were gender (P ≤ 0.05), body mass index (P ≤ 0.05), and self-reported regular exercise (P ≤ 0.01). The most impacted domains of sleep quality were sleep latency, sleep duration, and sleep disturbances. The prevalence of major depression was low (5%) and the rate of re-infarction was 27.2%. The prevalence of minimal to mild major depression with a potential of transitioning into major depression overtime was very high. Self-reported regular exercise (P ≤ 0.01) was the only significant predictor of depressive symptoms. Conclusion: The sleep quality of post myocardial infarction patients was poor and the prevalence of depression was low. There was no significant relationship between sleep quality or depression with re-infarction. Keywords: Aftercare, Depression, Myocardial infarction, Oman, Sleep initiation and maintenance disorders